Corrosion-resistant flame-retardant composite material pipe and preparation method thereof
By using halogen-free flame retardant propidene phosphonamide hydropyroxene and thiolbenzimidazole combined with nylon resin and glass fiber, corrosion-resistant flame-retardant composite material tubes are prepared, which solves the problem of the impact of toxic flue gases and mechanical properties of existing nylon materials during combustion, and achieves a comprehensive performance of high strength, high flame retardancy, corrosion resistance and environmental protection.
Patent Information
- Application Number
- CN202411797346.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing nylon materials are prone to toxic flue gas when burned, and the addition of flame retardant will affect the mechanical properties of the material. At the same time, nylon materials are prone to corrosion in a strong acid environment, making it difficult to meet the comprehensive performance requirements of flame retardant, corrosion resistance and environmental protection.
The halogen-free flame retardant propidene phosphonamide hydropyroxene and thiobenzimidazole were prepared by click chemical reaction, combined with nylon resin, glass fiber and other additives to prepare corrosion-resistant flame retardant composite material tubes.
It achieves high strength, high flame retardancy, corrosion resistance and environmental protection performance, and improves the stability and safety of nylon materials in harsh environments.
Smart Images

Figure CN119505529A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardant materials, and in particular to a corrosion-resistant flame retardant composite material pipe and a preparation method thereof. Background Art
[0002] Flame retardant pipes are suitable for liquid transportation with general working pressure in the fields of industry, agriculture, food, medicine, civil engineering, fishery, aquaculture, garden irrigation, etc. Such as: pneumatic pipes, hydraulic pipes, garden hoses, oil and water pipelines, oil exploration pipes, sandblasting pipes, peristaltic pump hoses, industrial robots, pneumatic tools, assembly plant air pressure tools, pressure delivery pipelines, can be used as vacuum straws, protective jackets or decorations for metal and electronic products. Nylon, also known as polyamide, is a thermoplastic polymer containing amide group repeating units in the main chain of the molecule. The amide group repeating unit can be obtained by condensation of dicarboxylic acid and diamine, or by opening of lactam. Nylon resin has good wear resistance, flexibility, dyeability and durability, and is widely used in clothing, stockings, clothing and industrial rope nets. As a nylon resin, in addition to the amide group repeating unit in the main chain of the molecule, it often contains a large number of methylene structural units. This causes nylon resin to burn easily, especially resin-reinforced nylon resin. Due to the candle wick effect, the limiting oxygen index is only 23%, and the vertical combustion level is no level. However, in many specific fields, there is an urgent need to provide nylon resins with better flame retardant properties.
[0003] At present, many flame retardants used in nylon materials are mainly halogen-based organic flame retardants such as decabromodiphenylethane and brominated polystyrene. Although these flame retardants have good flame retardant effects, they will produce toxic smoke during the combustion process, which can easily cause adverse effects on the human body and the environment. Although inorganic flame retardants have overcome many defects of halogen-based organic flame retardants, they need to be added in large quantities to achieve flame retardant effects, which seriously affects the mechanical properties of the material. In addition, nylon materials themselves have good chemical stability and corrosion resistance, have good tolerance to many chemical substances, and can maintain stability in general acid-base corrosive environments, but are still easily corroded under strong acid conditions. Therefore, for the development of flame-retardant nylon materials, we should not only pay attention to the environmental protection and flame retardant effects of the materials, but also consider the comprehensive performance of the materials. Summary of the invention
[0004] In view of the problems existing in the prior art, an object of the present invention is to provide a corrosion-resistant and flame-retardant composite material pipe and a preparation method thereof.
[0005] The purpose of the present invention is achieved by the following technical solutions: In a first aspect, the present invention provides a corrosion-resistant flame-retardant composite material pipe, calculated by weight, comprising: 60-80 parts of nylon resin, 15-25 parts of glass fiber, 5-18 parts of halogen-free flame retardant, 3-7 parts of compatibilizer, 2.1-3.5 parts of lubricant, 0.6-1.2 parts of antioxidant and 1-3 parts of antistatic agent.
[0006] Preferably, the nylon resin is one or a mixture of PA6, PA66, PA11, PA12, PA1010, and PA1212.
[0007] More preferably, the nylon resin is PA66 with a density of 1.15 g / cm 3 , the melt index is 18g / 10min (190℃, 2.16kg).
[0008] Preferably, the glass fiber is alkali-free glass fiber with a density of 2.6 g / cm 3 , with a diameter of 11-13μm and a length of 0.3-0.6mm.
[0009] Preferably, the flame retardant is prepared by a thiol-double bond click chemistry reaction of allenephosphonamidated hectorite and mercaptobenzimidazole.
[0010] Preferably, the compatibilizer is maleic anhydride grafted polyolefin elastomer (POE-g-MAH), with a grafting rate of 1.2% and a density of 0.87 g / cm 3 , the melt index is 1.8g / 10min (190℃, 2.16kg).
[0011] Preferably, the lubricant is a mixture of one or more of oxidized polyethylene wax, ethylene bisstearamide, paraffin wax and polyethylene wax.
[0012] Preferably, the antioxidant is a phenolic antioxidant, including one or more combinations of antioxidant 1098, antioxidant 1076, and antioxidant 1010.
[0013] Preferably, the antistatic agent is a mixture of one or more of polyether ester acetamide, polyether ester amide, polyethylene oxide, polyoxyethylene castor oil, and polyoxyethylene laurate.
[0014] Preferably, the preparation method of the halogen-free flame retardant comprises: S1, weighing hectorite powder and mixing it with a 30-50wt% ethanol solution, dispersing it evenly in an ultrasonic disperser, adding an aminosilane coupling agent, and then placing it in a water bath at 70-80°C, reflux stirring for 6-10h, and after the treatment, separating, washing and drying to obtain amino hectorite; S2, weigh allenephosphonyl chloride and add it to tetrahydrofuran, stir and dissolve, add amination hectorite, mix well, then drop triethylamine, stir at room temperature for 1-5h, then keep warm and reflux at 60-70°C for 6-12h, after the reaction is completed, remove the solvent, wash and dry to obtain allenephosphonyl amidation hectorite; S3. Weigh mercaptobenzimidazole and add it to anhydrous ethanol. After stirring to dissolve, add allenephosphonamidite hectorite and disperse evenly at room temperature. Add a photoinitiator and irradiate with an LED ultraviolet lamp while stirring continuously. React for 0.5-1.5 hours. After the reaction is completed, remove the solvent under reduced pressure to obtain a halogen-free flame retardant.
[0015] Preferably, in S1, the particle size of the hectorite powder is 10-15 μm, and the manufacturer is Zhejiang Huate New Materials Co., Ltd.
[0016] Preferably, in S1, the mass volume ratio of the hectorite powder, the aminosilane coupling agent and the ethanol solution is 1 g: (0.2-0.8) g: (10-20) mL.
[0017] Preferably, in S1, the mercaptosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.
[0018] Preferably, in S2, the mass volume ratio of amination hectorite, allenephosphonyl chloride, triethylamine and tetrahydrofuran is 1 g: (0.27-0.81) g: (0.13-0.26) g: (10-20) mL.
[0019] Preferably, in S3, the mass volume ratio of allenephosphonamidated hectorite, mercaptobenzimidazole and anhydrous ethanol is (1.1-1.5) g: (0.3-0.6) g: (30-50) mL.
[0020] Preferably, in S3, the photoinitiator is benzoin dimethyl ether, and the added amount is 3.5%-7.5% of the mass of mercaptobenzimidazole.
[0021] Preferably, in S3, the wavelength of the LED ultraviolet lamp is 325-390nm, and the light intensity is 1.3-2.6mW / cm 2 .
[0022] In a second aspect, the present invention provides a method for preparing a corrosion-resistant flame-retardant composite material pipe, comprising the following steps: Step 1, weighing other raw materials except glass fiber, mixing them in a blender, and stirring at a speed of 300-600 r / min until fully mixed to obtain a mixed raw material; Step 2, then introducing the mixed raw materials into a twin-screw extruder, adding glass fiber through side feeding, melt extrusion granulation, the extrusion temperature is 255-285°C, the screw speed is 80-120r / min, the aspect ratio L / D is 35-45, and a composite material masterbatch is obtained; Step 3, placing the composite material masterbatch in a mold for processing and forming to obtain a corrosion-resistant and flame-retardant composite material tube.
[0023] The beneficial effects of the present invention are: 1. The present invention prepares a flame retardant composite material pipe, the main material of the composite material pipe is nylon resin, glass fiber is used as the main reinforcing agent, the flame retardant used is an environmentally friendly organic-inorganic coated flame retardant, a compatibilizer is added to improve the compatibility of nylon resin with other materials, and lubricants, antioxidants, antistatic agents and other additives are also added. The final composite material pipe has high strength, high flame retardancy, corrosion resistance and environmental protection.
[0024] 2. In the present invention, the halogen-free flame retardant used is an environmentally friendly flame retardant that does not contain halogen, and is prepared by using allene phosphoamidated hectorite and mercaptobenzimidazole through a thiol-double bond click chemistry reaction. The preparation of allene phosphoamidated hectorite is to first activate the amino group of hectorite, and then react with allene phosphonyl chloride to form a phosphoamide group, thereby obtaining an organic-inorganic coating structure containing a double bond and a phosphoramide group.
[0025] 3. The flame retardant prepared by the present invention not only has excellent environmental protection and flame retardancy, but also greatly improves the cold resistance, impact resistance and acid resistance of nylon materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0027] Figure 1 Schematic diagram of scanning electron microscope of the halogen-free flame retardant prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0029] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0030] The present invention will be further described below in conjunction with the following examples. Example 1
[0031] A corrosion-resistant flame-retardant composite material pipe, calculated by weight, comprising: 70 parts of nylon resin PA66, 20 parts of alkali-free glass fiber, 12 parts of halogen-free flame retardant, 5 parts of compatibilizer POE-g-MAH, 2.8 parts of lubricant, 0.9 parts of antioxidant and 2 parts of antistatic agent.
[0032] Among them, the density of nylon resin PA66 is 1.15g / cm 3 , the melt index is 18g / 10min (190℃, 2.16kg); the density of alkali-free glass fiber is 2.6g / cm 3 , with a diameter of 11-13 μm and a length of 0.3-0.6 mm; the grafting rate of the compatibilizer POE-g-MAH is 1.2% and the density is 0.87 g / cm 3 , the melt index is 1.8g / 10min (190℃, 2.16kg); the lubricant is oxidized polyethylene wax; the antioxidant is antioxidant 1098; the antistatic agent is polyether ester acetamide.
[0033] The preparation method of the halogen-free flame retardant comprises: S1. Weigh the hectorite powder with a particle size of 10-15 μm and mix it with a 40wt% ethanol solution, disperse it evenly in an ultrasonic disperser, add γ-aminopropyltriethoxysilane, the mass volume ratio of hectorite powder, γ-aminopropyltriethoxysilane and ethanol solution is 1g:0.5g:15mL, then place it in a 75°C water bath, reflux and stir for 8h, and after the treatment, separate, wash and dry to obtain amino hectorite; S2, weigh allene phosphonyl chloride and add it to tetrahydrofuran, stir and dissolve, add amination hectorite, mix well, then dropwise add triethylamine, the mass volume ratio of amination hectorite, allene phosphonyl chloride, triethylamine and tetrahydrofuran is 1g:0.54g:0.2g:15mL, then stir at room temperature for 2h, then keep warm and reflux at 68°C for 8h, after the reaction is completed, remove the solvent, wash and dry to obtain allene phosphonyl amidated hectorite; S3. Weigh mercaptobenzimidazole and add it to anhydrous ethanol. Stir and dissolve it at room temperature. Then add allenephosphinamide hectorite and continue to disperse it evenly at room temperature. The mass volume ratio of allenephosphinamide hectorite, mercaptobenzimidazole and anhydrous ethanol is 1.3g:0.5g:40mL. Then, add benzoin dimethyl ether (5.5% of the mass of mercaptobenzimidazole) as an initiator. Use a wavelength of 365nm and a light intensity of 2.2mW / cm 2 The mixture was irradiated with an LED ultraviolet lamp while being continuously stirred for 1 hour. After the reaction, the solvent was removed under reduced pressure to obtain a halogen-free flame retardant.
[0034] The method for preparing the corrosion-resistant and flame-retardant composite material pipe comprises the following steps: Step 1, weighing other raw materials except glass fiber and mixing them in a mixer, stirring at a speed of 400 r / min until fully mixed to obtain a mixed raw material; Step 2, then introducing the mixed raw materials into a twin-screw extruder, adding glass fiber through side feeding, melt extrusion granulation, the extrusion temperature is 255-285° C., the screw speed is 100 r / min, the aspect ratio L / D is 40, and a composite material masterbatch is obtained; Step 3, placing the composite material masterbatch in a mold for processing and forming to obtain a corrosion-resistant and flame-retardant composite material tube. Example 2
[0035] A corrosion-resistant flame-retardant composite material pipe, calculated by weight, comprising: 60 parts of nylon resin PA6, 15 parts of alkali-free glass fiber, 5 parts of halogen-free flame retardant, 3 parts of POE-g-MAH, 2.1 parts of lubricant, 0.6 parts of antioxidant and 1 part of antistatic agent.
[0036] Among them, the density of alkali-free glass fiber is 2.6g / cm3 , diameter is 11-13μm, length is 0.3-0.6mm; the grafting rate of compatibilizer POE-g-MAH is 1.2%, and the density is 0.87g / cm 3 , the melt index is 1.8g / 10min (190℃, 2.16kg); the lubricant is paraffin; the antioxidant is antioxidant 1076; the antistatic agent is polyetheresteramide.
[0037] The preparation method of the halogen-free flame retardant comprises: S1. Weigh the hectorite powder with a particle size of 10-15 μm and mix it into a 30wt% ethanol solution. Disperse it evenly in an ultrasonic disperser, add γ-aminopropyltrimethoxysilane, the mass volume ratio of hectorite powder, γ-aminopropyltrimethoxysilane and anhydrous ethanol is 1g:0.2g:10mL, then place it in a 70°C water bath, reflux and stir for 6h, and after the treatment, separate, wash and dry to obtain amino hectorite; S2, weigh allene phosphonyl chloride and add it to tetrahydrofuran, stir and dissolve, add amination hectorite, mix well, then drop triethylamine, the mass volume ratio of amination hectorite, allene phosphonyl chloride, triethylamine and tetrahydrofuran is 1g:0.27g:0.13g:10mL, then stir at room temperature for 1h, then keep warm and reflux at 60°C for 6h, after the reaction is completed, remove the solvent, wash and dry to obtain allene phosphonyl amidated hectorite; S3. Weigh mercaptobenzimidazole and add it to anhydrous ethanol. Stir and dissolve it at room temperature. Then add allenephosphinamide hectorite and continue to disperse it evenly at room temperature. The mass volume ratio of allenephosphinamide hectorite, mercaptobenzimidazole and anhydrous ethanol is 1.1g:0.3g:30mL. Then, 3.5% of benzoin dimethyl ether by mass of mercaptobenzimidazole is added as an initiator. The wavelength is 365nm and the light intensity is 1.8mW / cm 2 The mixture was irradiated with an LED ultraviolet lamp while being continuously stirred for 0.5 h. After the reaction, the solvent was removed under reduced pressure to obtain a halogen-free flame retardant.
[0038] The method for preparing the corrosion-resistant and flame-retardant composite material pipe comprises the following steps: Step 1, weighing other raw materials except glass fiber and mixing them in a blender, stirring at a speed of 300 r / min until fully mixed to obtain a mixed raw material; Step 2, then introducing the mixed raw materials into a twin-screw extruder, adding glass fiber through side feeding, melt extrusion granulation, the extrusion temperature is 255-285° C., the screw speed is 80 r / min, the aspect ratio L / D is 35, and a composite material masterbatch is obtained; Step 3, placing the composite material masterbatch in a mold for processing and forming to obtain a corrosion-resistant and flame-retardant composite material tube. Example 3
[0039] A corrosion-resistant flame-retardant composite material pipe, calculated by weight, comprising: 80 parts of nylon resin PA12, 25 parts of alkali-free glass fiber, 18 parts of halogen-free flame retardant, 7 parts of POE-g-MAH, 3.5 parts of lubricant, 1.2 parts of antioxidant and 3 parts of antistatic agent.
[0040] Among them, the density of alkali-free glass fiber is 2.6g / cm 3 , diameter is 11-13μm, length is 0.3-0.6mm; the grafting rate of compatibilizer POE-g-MAH is 1.2%, and the density is 0.87g / cm 3 , melt index is 1.8g / 10min (190℃, 2.16kg); The lubricant is polyethylene wax; the antioxidant is a phenolic antioxidant, including antioxidant 1010; and the antistatic agent is a mixture of one or more of polyether ester acetamide, polyether ester amide, polyethylene oxide, polyoxyethylene castor oil, and polyoxyethylene laurate.
[0041] The preparation method of the halogen-free flame retardant comprises: S1. Weigh the hectorite powder with a particle size of 10-15 μm and mix it into a 50wt% ethanol solution, disperse it evenly in an ultrasonic disperser, add γ-aminopropyltriethoxysilane, the mass volume ratio of hectorite powder, γ-aminopropyltriethoxysilane and anhydrous ethanol is 1g:0.8g:20mL, then place it in a water bath at 80°C, reflux and stir for 10h, and after the treatment, separate, wash and dry to obtain amino hectorite; S2, weigh allene phosphonyl chloride and add it to tetrahydrofuran, stir and dissolve, add amination hectorite, mix well, then dropwise add triethylamine, the mass volume ratio of amination hectorite, allene phosphonyl chloride, triethylamine and tetrahydrofuran is 1g:0.81g:0.26g:20mL, then stir at room temperature for 5h, then keep warm and reflux at 70°C for 12h, after the reaction is completed, remove the solvent, wash and dry to obtain allene phosphonyl amidated hectorite; S3, weigh mercaptobenzimidazole and add it to anhydrous ethanol, stir and dissolve it at room temperature, then add allene phosphinamide hectorite, and continue to disperse it evenly at room temperature. The mass volume ratio of allene phosphinamide hectorite, mercaptobenzimidazole and anhydrous ethanol is 1.5g:0.6g:50mL, and then add benzoin dimethyl ether (7.5% of the mass of mercaptobenzimidazole) as an initiator, use a wavelength of 365nm, and the light intensity is 2.6mW / cm 2The mixture was irradiated with an LED ultraviolet lamp while being continuously stirred for 1.5 hours. After the reaction, the solvent was removed under reduced pressure to obtain a halogen-free flame retardant.
[0042] The method for preparing the corrosion-resistant and flame-retardant composite material pipe comprises the following steps: Step 1, weighing other raw materials except glass fiber, mixing them in a blender, and stirring at a speed of 600 r / min until fully mixed to obtain a mixed raw material; Step 2, then introducing the mixed raw materials into a twin-screw extruder, adding glass fiber through side feeding, melt extrusion granulation, the extrusion temperature is 255-285° C., the screw speed is 120 r / min, the aspect ratio L / D is 45, and a composite material masterbatch is obtained; Step 3, placing the composite material masterbatch in a mold for processing and forming to obtain a corrosion-resistant and flame-retardant composite material tube.
[0043] Comparative Example 1 A flame retardant composite material tube, which is different from Example 1 only in that the halogen-free flame retardant is replaced by hectorite powder.
[0044] Comparative Example 2 A flame retardant composite material tube, which is different from Example 1 only in that the halogen-free flame retardant is replaced by allene phosphinamidated hectorite (preparation is the same as Example 1).
[0045] Comparative Example 3 A flame retardant composite material tube, which is different from Example 1 only in that the halogen-free flame retardant is replaced by a mixture of hectorite powder and mercaptobenzimidazole, and the mass ratio of the hectorite powder to the mercaptobenzimidazole is 1.3:0.5.
[0046] Experimental example The composite material pipes prepared in Example 1 and Comparative Examples 1-3 were tested and compared in terms of performance. The relevant testing standards include: tensile strength refers to ISO 527-2:2012, simply supported beam notched impact strength refers to ISO 179-1:2010, limiting oxygen index refers to ISO 4589-2:1996, flame retardant grade refers to ANSI / UL-94-1985, acid resistance test: at room temperature, soak in 0.1 mol / L hydrochloric acid solution for 48 hours, and test the change rate of tensile strength; the test results are shown in Table 1: Table 1 Performance test results of different composite material pipes
[0047] It can be seen from Table 1 that the composite material pipe prepared in Example 1 of the present invention has higher tensile strength and impact strength at room temperature, and its impact strength performance at low temperature (-30°C) is also better than that of the comparative example. In addition, the composite material pipe prepared in Example 1 of the present invention also has better flame retardancy and acid resistance, indicating that its comprehensive performance is better and is suitable for use in more severe environments.
[0048] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0049] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A corrosion-resistant and flame-retardant composite material pipe, characterized in that: Calculated by weight, including: 60-80 parts of nylon resin, 15-25 parts of glass fiber, 5-18 parts of halogen-free flame retardant, 3-7 parts of compatibilizer, 2.1-3.5 parts of lubricant, 0.6-1.2 parts of antioxidant and 1-3 parts of antistatic agent; The halogen-free flame retardant is prepared by a click chemical reaction of sulfhydryl-double bond of allene phosphinamidated hectorite and mercaptobenzimidazole.
2. The corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: The nylon resin is one of PA6, PA66, PA11, PA12, PA1010, and PA1212, or a mixture of more thereof.
3. The corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber with a density of 2.6 g / cm 3 , with a diameter of 11-13 μm and a length of 0.3-0.6 mm; the compatibilizer is a maleic anhydride grafted polyolefin elastomer with a grafting rate of 1.2% and a density of 0.87 g / cm 3 The melt index at 190°C and 2.16kg is 1.8g / 10min.
4. The corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: The lubricant is a mixture of one or more of oxidized polyethylene wax, ethylene bisstearamide, paraffin, and polyethylene wax; the antioxidant is a phenolic antioxidant, including one or more combinations of antioxidant 1098, antioxidant 1076, and antioxidant 1010; the antistatic agent is a mixture of one or more of polyether ester amide, polyether ester amide, polyethylene oxide, polyoxyethylene castor oil, and polyoxyethylene laurate.
5. The corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: The preparation method of the halogen-free flame retardant comprises: S1. Weigh the hectorite powder and mix it with the ethanol solution, disperse it evenly in an ultrasonic disperser, add the aminosilane coupling agent, and then place it in a water bath at 70-80° C. and reflux and stir for 6-10 hours. After the treatment, separate, wash and dry to obtain the amino hectorite; S2, weigh allenephosphonyl chloride and add it to tetrahydrofuran, stir and dissolve, add amination hectorite, mix well, then drop triethylamine, stir at room temperature for 1-5h, then keep warm and reflux at 60-70°C for 6-12h, after the reaction is completed, remove the solvent, wash and dry to obtain allenephosphonyl amidation hectorite; S3. Weigh mercaptobenzimidazole and add it to anhydrous ethanol. After stirring to dissolve, add allenephosphonamidite hectorite and disperse evenly at room temperature. Add a photoinitiator and irradiate with an LED ultraviolet lamp while stirring continuously. React for 0.5-1.5 hours. After the reaction is completed, remove the solvent under reduced pressure to obtain a halogen-free flame retardant.
6. The corrosion-resistant and flame-retardant composite material pipe according to claim 5, characterized in that: In S1, the mass volume ratio of the hectorite powder, the aminosilane coupling agent and the ethanol solution is 1 g:(0.2-0.8) g:(10-20) mL; the mass fraction of the ethanol solution is 30%-50%; and the mercaptosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.
7. The corrosion-resistant and flame-retardant composite material pipe according to claim 5, characterized in that: In S2, the mass volume ratio of amination hectorite, allenephosphonyl chloride, triethylamine and tetrahydrofuran is 1 g: (0.27-0.81) g: (0.13-0.26) g: (10-20) mL.
8. The corrosion-resistant and flame-retardant composite material pipe according to claim 5, characterized in that: In S3, the mass volume ratio of allenephosphonamidated hectorite, mercaptobenzimidazole and anhydrous ethanol is (1.1-1.5) g: (0.3-0.6) g: (30-50) mL.
9. The corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: In S3, the photoinitiator is benzoin dimethyl ether, and the added amount is 3.5%-7.5% of the mass of mercaptobenzimidazole; the wavelength of the LED ultraviolet lamp is 325-390nm, and the light intensity is 1.3-2.6mW / cm 2 .
10. A method for preparing the corrosion-resistant and flame-retardant composite material pipe according to claim 1, characterized in that: The following steps are involved: Step 1, weighing other raw materials except glass fiber, mixing them in a blender, and stirring at a speed of 300-600 r / min until fully mixed to obtain a mixed raw material; Step 2, then introducing the mixed raw materials into a twin-screw extruder, adding glass fiber through side feeding, melt extrusion granulation, the extrusion temperature is 255-285°C, the screw speed is 80-120r / min, the aspect ratio L / D is 35-45, and a composite material masterbatch is obtained; Step 3, placing the composite material masterbatch in a mold for processing and forming to obtain a corrosion-resistant and flame-retardant composite material tube.
Citation Information
Patent Citations
Halogen-free flame retardant and glass fiber reinforced PA (polyamide) 66 composite material with acid and alkali resistance and preparation method of PA66 composite material
CN105062050A
Corrosion-resisting electric power material and preparation method thereof
CN107325392A
Anti-static heat-conducting flame-retardant composite material and preparation method thereof
CN112063163A
Polyamide composite resin composition for fuel tube
CN114075384A
Polyamide material with improved long-term use performance
CN115244121A